PERANCANGAN PROTOTYPE WEDDING ORGANIZER SYAR’I BERBASIS WEB - Hilmansyah Gani; yulanda yunus (JSAI (Journal Scientific and Applied Informatics), 2024)
In the current digital era, there is a growing demand for wedding services that adhere to Sharia or Syar’i principles. This research aims to design a web-based Wedding Organizer prototype that meets Syar’i criteria. The system development methodology involved an initial survey to identify user needs and preferences, followed by the design, development, and evaluation phases of the prototype. The result is a web-based Wedding Organizer prototype that not only simplifies the wedding planning process but also ensures that every aspect aligns with Syar’i principles. Overall, there are 13 interface design prototypes, consisting of the Home Page, Login Page, Customer Registration Data Page, Product Type Data Page, Product Data Page, Package Data Page, Customer Order Data Page, Payment Data Page, Customer Order Execution Page, Customer Data Page, Payment Account Page, Customer Order List Page, and Azariah Wedding Documentation Page. This prototype is expected to be an innovative solution for couples who want to have a wedding in accordance with Islamic teachings.